Relationship Between Sepsis Phenotypes and Treatment Characteristics of Patients with Viral and Bacterial Pneumonia - I. A. Ruslyakova; E. Z. Shamsutdinova; L. B. Gaikovaya (Общая реаниматология)
New subgroups of patients with severe community-acquired pneumonia (SCAP) are hardly predicted by the use of clinical covariates; clusterization may signiﬁcantly improve diagnostic approaches and facilitate the adaptation of speciﬁc treatment modalities to patient’s individual characteristics.The aim of the study. To identify linking the sepsis phenotype in patients with SCAP and preferable treatment option to forecasting the outcome and improve treatment results.Materials and methods. Case histories of 664 of intensive care unit (ICU) patients with sepsis (2016–2023) from I. I. Mechnikov Northwestern State Medical University were analyzed. The study included 568 (85.5%) patients with viral SCAP (SCAPv group) and 96 (14.5%) patients with bacterial SCAP (SCAPb group). Sepsis phenotypes were identiﬁed using algorithm proposed by Seymour C.W. et al. In SCAP cases associated with COVID-19 infection (n=293, 51.6%) patients received genetically engineered biological therapy (GIBT). The study compared two cohorts of patients: those who received GIBT and did not receive GIBT. Data were statistically processed using the Statistica 10.0 and SPSS software packages.Results. Analysis revealed 4 sepsis phenotypes: α- (N=323, 48.6%); β- (N=128, 19.3%); γ- (N=87, 13.1%); δ - (N=126, 19%). The majority of SCAPv group patients — 295 (51.9%) — had α-phenotype of sepsis, while δ -phenotype prevailed in the SCAPb group — 53 (55.2%). The proportion of patients receiving GIBT and exhibiting α- sepsis phenotype dominated over other sepsis phenotypes: 61.8% of patientspossesed α- phenotype, whereas β-, γ- and δ -phenotypes were determined in 16% , 12.6%, and 9.6% of GIBT patients, respectivelty (P<0.05). The best eﬀect of using monoclonal antibodies to interleukin-6 receptors as a GIBT was obtained in patients with the α-phenotype sepsis and COVID-19-associated SCAP: 87.5% favorable outcomes, P=0.0419. Rate of bacterial sepsis was signiﬁcantly lower in patients with α- and δ -phenotypes of sepsis receiving GIBT vs those who did not receive this therapy: 12.71% vs 23.2% of patients with α-phenotype, P=0.0131; 25.0% vs 70.41% of patients with δ -phenotype, P=0.0254, respectively.Conclusion. Diﬀerences in sepsis phenotype between patients with viral or bacterial SCAP may stratify patients for diﬀerent therapeutic management and more accurately predict potential complications and unfavorable outcome.